Endoscopic Ultrasound–Guided Fine-Needle Aspiration Microhistology in Asymptomatic and Symptomatic Pancreatic Cystic Lesions. Issue 4 (April 2020) - Vaiciunas, Spencer; Taglieri, Eloy; Micelli-Neto, Otávio; Brunaldi, Mariângela Ottoboni; Venco, Filadélfio; Goldman, Suzan Menasce; Kemp, Rafael; dos Santos, José Sebastião; Ardengh, José Celso
Abstract : Objective: This study aimed to analyze the usefulness of endoscopic ultrasound–guided fine-needle aspiration (EUS-FNA) microhistology to detect malignancy in pancreatic cystic lesions (PCLs). Methods: Patients with PCLs were identified and submitted to EUS-FNA from January 2010 to January 2017. The percentage of samples suitable for diagnostic classification by microhistology and the positive and negative likelihood ratios to detect malignancy in asymptomatic (APC) and symptomatic (SPC) PCLs were determined. Results: Endoscopic ultrasound–guided fine-needle aspiration was performed in 510 patients. The resulting material was processed by microhistology and useful for diagnosis in 432 (84.2%). Clinical characteristics of APC (341) and SPC (169) revealed that APC patients were younger ( P = 0.004) and had smaller PCLs (23 vs 35 mm; P < 0.001). In APC, we found more preneoplastic (38.7% vs 30.2%; P = 0.0016) and a lower number of malignant PCLs (8.2% vs 24.3%; P < 0.001). In APC and SPC, the sensitivity, specificity, positive predictive value, negative predictive value, and accuracy of microhistology to detect malignancy were 71.4%, 99.7%, 95.2%, 97.5%, and 97.4% ( k = 0.80) and 58.5%, 96.9%, 85.7%, 87.9%, and 87.6%, respectively. Conclusions: Endoscopic ultrasound–guided fine-needle aspiration was technically feasible. Microhistology was especially useful to detect neoplastic or malignant PCLs in APC patients.